Factores del bajo rendimiento académico en física en la Carrera de Pedagogía de las Ciencias de Experimentales: Matemáticas y Física - Contreras Arévalo, Jubena Cecibel (2024)
This research focuses on studying the factors related to low academic performance in the area of physics, whose objective is to analyze the factors associated with the low performance of students of the Pedagogy of Experimental Sciences: Mathematics and Physics within the period 2023 2S. In the theoretical referent, the following elements have been considered: institutional, pedagogical, sociocultural, socioeconomic factors, and learning styles. The methodology has a quantitative approach with a non-experimental design of the relational descriptive level, applying a survey for data collection. The population consisted of 50 students whose selection criterion was students considered to have low performance in subjects related to the area of physics from the first to the eighth semester in the period 2023 2S. No sample was considered because this was a descriptive study. Data processing used descriptive statistical techniques combined with pivot tables, for which the Excel tool was used. The results show that the most recurrent factors concerning low academic performance are pedagogical, socioeconomic, and some others with less frequency; with this background, it is recommended that teachers apply strategies to develop the four learning skills, and students are suggested to perform the activities autonomously, avoid plagiarism, request and attend tutorials with teachers.